The Effect of Foot Position on the Muscles Activity of the Shoulder and Trunk Muscles in Load Lifting - Arezoo Noori; Nader Farahpour; Mahdi Majlesi (Islamic Azad University, Hamedan Branch, 2016)
Objective: This study aimed to investigate the effects of leg positioning on the activity of shoulders and body while lifting weights. Methods: Employing an electromyography set (BTS free EMG 300) and surface electrodes, the activity of such muscles as biceps, triceps, anterior, medial and posterior deltoid, trapezius and erector spinae, while lifting a weight weighing %15 of body mass, in three leg positions (straight, bending and a leg on a step), were measured. Each muscle`s RMS data, during performing the skills, were divided by the amount of maxinmum voluntary isometric contraction (MVIC) then multiplied by 100. Repeated Measurewas used to analysis the data at the significance level of (p<0.05) in SPSS 16. Results: The results showed no significant difference among the activity of such muscles as biceps, triceps, anterior, medial and posterior deltoid, trapezius and erector spinae in three different positions. However, there existed a significant different between the different pectoral gridle and erector spinae muscles in terms of their intensity of activity (p=0.01). The maximum of intensity of activity was respectively assigned to erector spinae, anterior deltoid, medial deltoid, trapezius, posterior deltoid, bicepts and tricepts. Moreover, the comparison of the activity of the muscle L3 in the three different leg positions in lifting a weight did not show a significant difference (p=0.05). Conclusion: The way of lifting the object does not lead to a significant difference in the intensity of the activity of different muscles.